2018
DOI: 10.14507/epaa.26.3825
|View full text |Cite
|
Sign up to set email alerts
|

The Seal of Biliteracy: Considering equity and access for English learners

Abstract: The Seal of Biliteracy is a grass-roots language policy initiative that is sweeping across the United States. An award affixed to high school graduates’ transcripts and diplomas, the overarching purpose of the policy is to promote and foster students’ bilingualism and biliteracy in K-12 schools. Initiated in California in 2011, the policy has been modified significantly as stakeholders in 32 different states have drafted, passed, and enacted similar legislation in recent years. On its surface, the policy appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 4 publications
0
29
0
Order By: Relevance
“…The Minnesota seals legislation has been praised for its explicit focus on supporting the home languages of English learners (Heineke et al, 2018), and the state has been considered a model for actively working to expand the number of languages in which assessments are available (Davin & Heineke, 2018). Indeed, while there is no funding for testing tied to the legislation, the MDE closely collaborated with ACTFL in efforts to develop tests for the 12 most common home languages in the state (including Somali, Hmong, Vietnamese, Karen, Oromo, Amharic, Laotian, and Khmer), plus Ojibwe and Dakota, languages Indigenous to the state of Minnesota.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Minnesota seals legislation has been praised for its explicit focus on supporting the home languages of English learners (Heineke et al, 2018), and the state has been considered a model for actively working to expand the number of languages in which assessments are available (Davin & Heineke, 2018). Indeed, while there is no funding for testing tied to the legislation, the MDE closely collaborated with ACTFL in efforts to develop tests for the 12 most common home languages in the state (including Somali, Hmong, Vietnamese, Karen, Oromo, Amharic, Laotian, and Khmer), plus Ojibwe and Dakota, languages Indigenous to the state of Minnesota.…”
Section: Resultsmentioning
confidence: 99%
“…Subtirelu et al (2019) suggest that the path to be verified as biliterate might be more challenging for English learners, who must take formal exams to assess their multilingual ability. And third, in many states, the availability and nature of the assessments are potentially biased toward English speakers who are studying a widely taught world language such as Spanish or French (Heineke et al, 2018). Many states reportedly lack assessments for all languages spoken by students, especially those with smaller numbers of speakers worldwide or with fewer written materials.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is important for SoBL administrators to ensure access for speakers of languages not frequently offered through mainstream high schools, since a policy that advocates for the celebration and recognition of the United States' bilingual resources must strive to acknowledge the country's linguistic diversity in full. Multiple studies (Heineke, Davin, & Bedford, 2018; Heineke, Davin, & Dávila, 2019; Subtirelu et al, 2019) have concluded that local policies and practices around the SoBL tend to inadvertently advantage English‐dominant students, particularly in the following ways: (a) certain states ask ELs to provide more sources of evidence to demonstrate their English proficiency than other SoBL candidates, (b) the level of English proficiency demanded is generally higher than that of the other language, and (c) the standardized tests required to demonstrate proficiency for the SoBL are overwhelmingly designed for students studying in foreign or world language classes, potentially disadvantaging heritage speakers. The purpose of this paper is to highlight how partnerships with community‐based institutions can serve as important avenues for expanding access to the SoBL, particularly for heritage speakers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study explores the emerging role of community HL schools in the SoBL initiative, through the lens of local actors. While preliminary research has been done on the promotion and implementation of the SoBL in high schools across different states (Davin & Heineke, 2017; Davin, Heineke, & Egnatz, 2018; Heineke et al 2018; Subtirelu et al, 2019), there has been only one study to date on the involvement of community HL schools in the initiative, which focuses on the case of a Tamil Saturday school in Minnesota (Davin, Hancock, & Mariyappan, 2019). Despite this lack of research attention, community‐based schools are emerging as an important constituency which can be central to the initiative's expansion.…”
Section: Literature Reviewmentioning
confidence: 99%